The Role of Exercise Training in Cardiometabolic Disorder Patients - M Ridwan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Cardiometabolic diseases are still major causes of mortality in modern society. Despite advanced ......